Film in the Advanced Composition Classroom: A Tapestry of Style. - Durst, Pearce (Composition Forum)
This article advances film as worthy of rhetorical inquiry and deserving of more sustained attention in the advanced composition classroom. The first section identifies various approaches to the "language" of film, which can be adopted to navigate the technical, rhetorical, and cultural concerns needed to compose informed multimodal compositions. The second section, montage style editing, as it appears in The Odessa Steps Sequence from Battleship Potemkin by Sergei Eisenstein, establishes that an awareness of "style" can bridge the gap between print and new media literacy. The third section outlines one advanced writing assignment called a "montage tap essay" in which students use a free online platform called Tapestry to create an interactive essay that ostensibly takes into consideration the particular cinematic affordances of editing, design, and writing.